1998
DOI: 10.1055/s-2007-973589
|View full text |Cite
|
Sign up to set email alerts
|

Complete Remission of a Diffuse Pontine Glioma

Abstract: A patient is described in whom a large diffuse glioma of the pons extending into the midbrain was diagnosed at the age of 2 years. Biopsy showed a fibrillary astrocytoma. After shunting of a hydrocephalus, the clinical symptoms abated without conventional therapy. Repeated MRI studies showed a continuous decrease of the tumour which was no longer visible when the patient was 6.6 years old. In reviews on spontaneous remissions of oncologic disorders we were unable to find a case of a biologically benign brain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 2 publications
0
20
0
9
Order By: Relevance
“…12 Lenard et al have described 1 patient with diffuse pontine glioma diagnosed at age 23 months who experienced complete resolution of his tumor at age 6.6 years. 19 This patient presented with signs and symptoms for 12 months. Stereotactic biopsy of the tumor yielded a diagnosis of fibrillary astrocytoma (World Health Organization grade 2).…”
Section: Discussionmentioning
confidence: 98%
“…12 Lenard et al have described 1 patient with diffuse pontine glioma diagnosed at age 23 months who experienced complete resolution of his tumor at age 6.6 years. 19 This patient presented with signs and symptoms for 12 months. Stereotactic biopsy of the tumor yielded a diagnosis of fibrillary astrocytoma (World Health Organization grade 2).…”
Section: Discussionmentioning
confidence: 98%
“…Brain tumors that show spontaneous regression include low grade tumors of the hypothalamicchiasmatic region and diffuse brainstem gliomas. Lenard et al and Thompson et al have reported rare cases of spontaneous remission of diffuse brainstem lesions [10,11]. Schmandt et al reviewed 22 patients in whom regression of astrocytomas had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Most tumors occurred in the visual pathway system with extension into the hypothalamus; some were restricted to the hypothalamus or were located in the thalamus and brainstem. Ten cases were examined pathologically with a diagnosis of juvenile pilocytic astrocytoma in 7 [4, 8, 10], grade I astrocytoma in 1 [11]and grade II astrocytoma in 2 [7, 12]. In the remaining 12 cases, the diagnosis of glioma was presumptive or not further specified.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the regression, 7 of the 22 patients underwent a biopsy of their tumor [4, 10, 11, 12], 4 patients underwent partial tumor resection [7, 8, 13], 1 had a resection of an unrelated cerebral astrocytoma [5]and 3 received ventriculoperitoneal shunts at the time of their biopsy or surgery [8, 11, 12]. However, our case and others showed regression quite some time after surgery, suggesting that involution may not be directly related to the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation